2020
DOI: 10.36740/wlek202004122
|View full text |Cite
|
Sign up to set email alerts
|

Early Pregnancy and Endothelial Dysfunction

Abstract: The aim is to analyze the value of endothelial dysfunction markers during pregnancy. Materials and methods: We have examined 153 pregnant women to identify endothelial dysfunction markers of endothelin-1, nitrogen oxide (NO) that have been studied using immunoenzymometric sets for an uncomplicated and complicated pregnancy. Results: We found that the concentration of endothelin-1 repeatedly exceeded the rates in pregnant women with miscarriages than during physiological pregnancy. The diametrically opposite pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, endothelial dysfunction, characterised by imbalances of vasoconstrictor/vasodilator factors, involves increases in blood coagulation potential (hypercoagulation) leading to uterine vessel vasoconstriction, platelet aggregation activation and resulting in final miscarriage [ 418 ]. Dubyk et al compared ET-1 and NO serum levels in pregnancies with a risk of miscarriage, spontaneous abortion and non-developing pregnancies versus physiological pregnancies [ 418 ]. They reported a significant increase in ET-1 and decreased NO levels in all groups compared to the control group.…”
Section: Et-1 and Pregnancy Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, endothelial dysfunction, characterised by imbalances of vasoconstrictor/vasodilator factors, involves increases in blood coagulation potential (hypercoagulation) leading to uterine vessel vasoconstriction, platelet aggregation activation and resulting in final miscarriage [ 418 ]. Dubyk et al compared ET-1 and NO serum levels in pregnancies with a risk of miscarriage, spontaneous abortion and non-developing pregnancies versus physiological pregnancies [ 418 ]. They reported a significant increase in ET-1 and decreased NO levels in all groups compared to the control group.…”
Section: Et-1 and Pregnancy Complicationsmentioning
confidence: 99%
“…They reported a significant increase in ET-1 and decreased NO levels in all groups compared to the control group. This indicated that endothelial dysfunction was likely the cause of miscarriage in these women, serving ET-1 and NO as potential markers for endothelial dysfunction [ 418 ].…”
Section: Et-1 and Pregnancy Complicationsmentioning
confidence: 99%